Insect Diversity Pests and Natural Enemies in Soybean (Glycine max (l.) Merrill) Fields Manggoapi Experimental Garden Manokwari to Increase Community Income - Sutiharni Sutiharni; Cindynia Rivera Kurni; Andrean Wospakrik; Yacob Bodang; Adelin E. Tanati; Decky C. Erari (Budapest International Research and Critics University, 2022)
Soybean is one of the food crops that are high in protein. The protein content of Indonesian soybean varieties varies from 36.9 to 45.6%, 33% calories and 18% fat, while some soybean varieties in the world contain up to 50% protein and more than 20% oil. Yellow soybeans are generally used as raw materials for tempeh and tofu, while black soybeans are used as raw materials for soy sauce. This plant is widely used as a food ingredient as well as industrial raw material and animal feed. One of the obstacles to efforts to increase production is the attack of various pests that can damage plants from growing until harvest time. In Indonesia, more than 111 species of arthropods are pests, 53 species are not targeted, 61 species are predators and 41 species are parasitoids. Pests are an obstacle in maintaining and increasing agricultural production, both in terms of quality and quantity, even to the point of thwarting harvests. Pests are nuisance organisms that cause economic impacts or losses and cause yield losses. Natural enemies in a good balance of nature are always successful in controlling pest populations. The method used is purposive sampling method and time series data from the Central Statistics Agency (BPS) and the Food and Angricultural Organization (FAO); tabulated analysis. The results of the research on types of insect pests and natural enemies in the vegetative and reproductive phases, there were 13 types of insect pests and 5 types of natural enemies found in soybean plantations. One of the approaches to increasing soybean production for people in Indonesia is through integrated pest control (IPM).